1996
DOI: 10.1111/j.1476-5381.1996.tb15279.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ assessment of the role of the β1, β2‐ and β3‐adrenoceptors in the control of lipolysis and nutritive blood flow in human subcutaneous adipose tissue

Abstract: 1 The involvment of #I-, 12-and /3-adrenoceptors in the control of lipolysis and nutritive blood flow was investigated in abdominal subcutaneous adipose tissue of healthy young adults by use of an in situ microdialysis technique.2 Dialysis probes were infused either with isoprenaline (non-selective f,-adrenoceptor agonist), CGP 12,177 (selective #3-adrenoceptor agonist having 3,-/12-antagonist properties), dobutamine (selective 13,-adrenoceptor agonist) or terbutaline (selective 132-adrenoceptor agonist). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
97
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(110 citation statements)
references
References 39 publications
11
97
0
2
Order By: Relevance
“…It must be emphasized that, while the ␤ 3 -AR plays a pivotal role in rodent white or brown adipose tissue, it is expressed at much lower levels in humans (48 -50). Recent studies performed in vivo have shown that the ␤ 3 -AR is able to mediate lipolysis in subcutaneous fat in humans (51,52), but its role appears secondary as compared with that of ␤ 1 -or ␤ 2 -ARs. It is thus likely that a potential regulation by TNF-␣ of the ␤ 3 -AR in human adipocytes would not cause marked functional consequences.…”
Section: Table IV Effect Of Tnf-␣ Treatment On the Lipolytic Activitymentioning
confidence: 99%
“…It must be emphasized that, while the ␤ 3 -AR plays a pivotal role in rodent white or brown adipose tissue, it is expressed at much lower levels in humans (48 -50). Recent studies performed in vivo have shown that the ␤ 3 -AR is able to mediate lipolysis in subcutaneous fat in humans (51,52), but its role appears secondary as compared with that of ␤ 1 -or ␤ 2 -ARs. It is thus likely that a potential regulation by TNF-␣ of the ␤ 3 -AR in human adipocytes would not cause marked functional consequences.…”
Section: Table IV Effect Of Tnf-␣ Treatment On the Lipolytic Activitymentioning
confidence: 99%
“…Adrenergic receptors expressed within adipose tissue have been extensively studied. 78,79 Obesity is associated with changes in adrenoceptor numbers and subtypes. 80 This suggests that the autonomic signals to adipose tissue are modulated in response to energy stores and adipocyte size.…”
Section: Innervation Of White Adipose Tissuementioning
confidence: 99%
“…Much initial attention focussed on a role of β 3 -adrenoceptors in the regulation of adipocyte function, but later studies showed that its important role in rodents is not paralleled by a major role in human adipocytes (Barbe et al 1996;Rosenbaum et al 1993). Meanwhile, a role for β 3 -adrenoceptors has been established in blood vessels (Guimaraes and Moura 2001;Rozec and Gauthier 2006) and the urinary bladder (Michel and Vrydag 2006).…”
mentioning
confidence: 99%